Primary pulmonary Ewing sarcoma: a rare case report - Arslan, Remzi; Tamer, Harika Derya; Temtek, Ayşe Nur (The European Research Journal, 2024)
Ewing sarcoma (ES) is a malignant soft tissue tumor that consists of undifferentiated neuroectodermal cells. The anatomical sites of ES are commonly the pelvis and long bones. Metastasis is the cause of the most prevalent pulmonary ES. The primary lung origin of ES is extremely uncommon. Here, we report a rare case of primary pulmonary ES diagnosed from cytology and biopsy material. A chest X-ray revealed a lesion with a 9 × 7.5 cm diameter in the pericardiac area of the right lung. Clinical and radiological examinations (computed tomography and positron emission tomography) demonstrated that the lesion was a primary lesion. No distant metastasis was detected. Bronchoscopy-guided fine-needle aspiration and cytological analysis of the lesion revealed uniformly shaped small round cell morphology. Immunohistochemistry performed on the cell block produced positive results for CD99 and FLI-1. These immunohistochemical findings support the ES diagnosis.